Is narcolepsy an antibody-mediated autoimmune disease - Thebault, S (2012)
Narcolepsy is a lifelong sleep disorder of unknown cause. Patients experience excessive daytime sleepiness (EDS) in conjunction with the pathognomonic symptom of cataplexy, which is a sudden bilateral loss of motor tone triggered by positive emotion. Central to the pathology of narcolepsy-cataplexy is the loss of orexin-secreting neurons in the hypothalamus and the concomitant loss of orexin neuropeptide in the cerebrospinal fluid (CSF). The cause is thought to be autoimmune, mainly because of the tight association with HLA DQB1*0602. However, there is no direct evidence to support this hypothesis. Since 2010, a particular H1N1 vaccine has been implicated as a rare trigger of narcolepsy-cataplexy in children. Post-vaccination cases have a particularly abrupt onset, and may provide new insights into disease aetiology. This thesis explored the possibility of a humoral immune cause. Tests for the presence of antibodies directed towards neuronal antigens were performed on 17 sera/CSF pairs from children with recent onset narcolepsy-cataplexy as well as unpaired samples and those from adults and controls. Methods included a cell-based candidate antigen approach, antibody-screening techniques using rat brain tissue and neuronal cultures, and testing for biomarkers of autoimmunity. There was no consistent evidence of autoantibodies to a specific antigen in a high proportion of patients, but immunoreactivity to neuronal antigens, including unidentified antigens on the surface of neurons in culture, was identified in some samples. This large narcolepsy cohort included recent-onset and post-vaccination cases, patients in whom putative autoantibodies are most likely to be found. Immunoreactivity in some cases provides preliminary evidence for autoantibodies which needs to be followed up. Further strategies are required to investigate the aetiological mechanisms underpinning narcolepsy-cataplexy, including addressing the possibility of T cell-mediated damage.